Isoprene emission aids recovery of photosynthetic performance in transgenic Nicotiana tabacum following high intensity acute UV-B exposure - Centritto, Mauro (Plant science : an international journal of experimental plant biology, 2014)
Copyright © 2014 Elsevier Ireland Ltd. All rights reserved.